2017
DOI: 10.1080/16549716.2017.1340253
|View full text |Cite
|
Sign up to set email alerts
|

Management of noma: practice competence and knowledge among healthcare workers in a rural district of Zambia

Abstract: Background: Noma is an infectious but opportunistic disease that often results in severe facial disfigurements and mortality if untreated. As noma progresses quickly, early detection and treatment are important to prevent its development.Objectives: The objective of this study was to investigate primary healthcare workers’ knowledge and management of noma in a rural part of Zambia.Methods: A cross-sectional self-completed survey was conducted among 35 healthcare workers from two district hospitals and 15 rural… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
22
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 23 publications
(23 citation statements)
references
References 20 publications
(35 reference statements)
1
22
0
Order By: Relevance
“…More importantly, the lack of knowledge related to the diagnosis and therapy of Hp was concerning. This study replicates findings of multiple previous studies in Africa about general knowledge of bacterial diseases being low among healthcare workers [17,18]. When we consider the inconsistent practices for the management of chronic dyspepsia, coupled with a limited knowledge of possible etiologies and appropriate Hp eradication regimens, it stands to reason that this population could be at risk of antibiotic resistant infection.…”
Section: Discussionsupporting
confidence: 85%
“…More importantly, the lack of knowledge related to the diagnosis and therapy of Hp was concerning. This study replicates findings of multiple previous studies in Africa about general knowledge of bacterial diseases being low among healthcare workers [17,18]. When we consider the inconsistent practices for the management of chronic dyspepsia, coupled with a limited knowledge of possible etiologies and appropriate Hp eradication regimens, it stands to reason that this population could be at risk of antibiotic resistant infection.…”
Section: Discussionsupporting
confidence: 85%
“…27 Many cases will never seek care, and, even if they do, noma is unknown to many healthcare workers in endemic areas. 28 The condition may thus go undiagnosed, and rapid detection with opportunities for early treatment through improved oral hygiene, nutritional support and antibiotics, may be missed.…”
Section: Discussionmentioning
confidence: 99%
“…Noma is a difficult disease to study due to its rapid progression, reported high mortality rate, and the remote location of affected patients [ 1 ]. Noma is infrequently taught in medical, nursing, or tropical medicine courses, and this leads to a lack of knowledge about noma among healthcare workers [ 6 , 7 ]. Affected patients often lack access to quality healthcare, and, even when healthcare is sought, noma is regularly misdiagnosed due to a lack of knowledge about noma among healthcare workers, leading to underreporting of the disease [ 6 , 7 ].…”
Section: Introductionmentioning
confidence: 99%
“…Noma is infrequently taught in medical, nursing, or tropical medicine courses, and this leads to a lack of knowledge about noma among healthcare workers [ 6 , 7 ]. Affected patients often lack access to quality healthcare, and, even when healthcare is sought, noma is regularly misdiagnosed due to a lack of knowledge about noma among healthcare workers, leading to underreporting of the disease [ 6 , 7 ]. Patients with noma thus remain invisible within their communities, the health systems that are supposed to serve them, and the global community, feeding into the poor understanding of this disease and its subsequent neglect.…”
Section: Introductionmentioning
confidence: 99%